Math, asked by aditi012, 1 year ago

solve the equation 4(3p+2) - 5(6p-1) = 2(p-8) -6(7p-4)​

Answers

Answered by Rayanwani
4

4(3p+2)-5(6p-1)=2(p-8)-6(7p-4)

12p +8-30p+5=2p-16-42p+24

12p-2p+42p-30p=-16+24-8-5

22p=6

p=6/22

p=3.66


aditi012: is it ryt?
Answered by meenu011279gmailcom
3

4(3p+2) - 5(6p - 1) = 2(p - 8) - 6(7p-4)

=12p+8-30p+5 = 2p-16-42p+24

=12p-30p-2p+42p = - 16+24-8-5

=54p-32p = 24-29

=22p = - 5

= p = - 5/22

Ans. p = - 5/22


aditi012: it is wrong
aditi012: sorry
aditi012: first ans by ryanwani is ryt
Similar questions